THE IMPACTS OF REMITTANCES ON ECONOMIC GROWTH OF PAKISTAN THROUGH TRANSMISSION CHANNEL OF INVESTMENT - Gilal Ashfaque Ali; Dr. Nor Asmat Ismail; Dr Siti 'Aisyah Baharudin (International Journal of Contemporary Issues in Social Sciences, 2024)
The main purpose of this study was to assess the impacts of remittances through transmission channel of investment on economic growth of the Pakistan. For this purpose, the time series data obtained from World development indicator was analyzed through ARDL bound test. The findings demonstrate that remittances have positive and significant impacts on economic growth of Pakistan especially through transmission channel of investment. Based on the findings, it is recommended that government of Pakistan should take concrete and effective measures to ensure the transmission of remittances through formal channel and use the received funds in high returned investment projects to stimulate economic growth in Pakistan. This study is an original work developed from PhD thesis and is first ever study to be conducted in case of Pakistan by considering an investment as a transmission channel through which remittances can affect economic growth.